Pemanfaatan Kode Dengan Walikelas Untuk Meningkatkan Partisipasi Peserta Didik Dalam Melaksanakan BDR - Hema Hujaemah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
The Covid-19 pandemic, which has spread to almost all parts of Indonesia, has not yet been declared complete. This is what causes the face-to-face learning process in schools to turn into Distance Learning (BDR/PJJ). Ideally, in any situation and condition the learning process can run normally, but in reality this is not the case. Problems arise, namely the low participation/involvement of students in implementing BDR. This data was obtained based on reports from homeroom teachers, on average 8 out of 32 students had attendance, assignments and daily test scores still below 50%. This problem cannot be ignored, the principal needs to immediately find a solution. Coordination, Discussion, and Evaluation abbreviated as KODE with homeroom teachers was chosen as an action, to help homeroom teachers improve their competence in serving students who are constrained in implementing BDR. KODE was implemented through school action research which consisted of two cycles. Each cycle consists of two meetings consisting of planning, implementation, and reflection. The purpose of this research is to increase the participation of students in implementing BDR. Activities to direct, motivate, and provide solutions through KODE, can improve the competence of homeroom teachers in the learning process and managing their classes. This is evidenced by an increase in the participation of class VII students by 86%, class VIII by 90%, and class IX by 83%. The results of this study are recommended to other school principals as an effort to empower homeroom teachers to overcome the problem of lack of student participation in implementing BDR.